Swedish traveller with Plasmodium knowlesi malaria after visiting Malaysian Borneo - Bronner, U; Divis, Paul Cliff Simon; Farnert, A.; Singh, B. (BioMed Central Ltd, 2009)
Plasmodium knowlesi is typically found in nature in macaques and has recently been recognized as the fifth species of Plasmodium causing malaria in human populations in south-east Asia. A case of knowlesi malaria is described in a Swedish man, who became ill after returning from a short visit to Malaysian Borneo in October 2006. His P. knowlesi infection was not detected using a rapid diagnostic test for malaria, but was confirmed by PCR and molecular characterization. He responded rapidly to treatment with mefloquine. Evaluation of rapid diagnostic kits with further samples from knowlesi malaria patients are necessary, since early identification and appropriate anti-malarial treatment of suspected cases are essential due to the rapid growth and potentially lifethreatening nature of P. knowlesi. Physicians should be aware that knowlesi infection is an important differential diagnosis in febrile travellers, with a recent travel history to forested areas in south-east Asia, including short-term travellers who tested negative with rapid diagnostic tests.